2020
DOI: 10.3390/microorganisms8020165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Obstructive Pulmonary Disease on Incidence, Microbiology and Outcome of Ventilator-Associated Lower Respiratory Tract Infections

Abstract: Objectives: To determine the impact of chronic obstructive pulmonary disease (COPD) on incidence, microbiology, and outcomes of ventilator-associated lower respiratory tract infections (VA-LRTI). Methods: Planned ancillary analysis of TAVeM study, including 2960 consecutive adult patients who received invasive mechanical ventilation (MV) > 48 h. COPD patients (n = 494) were compared to non-COPD patients (n = 2466). The diagnosis of ventilator-associated tracheobronchitis (VAT) and ventilator-associated pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…However, what is clinically useful is that PA occurred in Early onset-VAP (Eo-VAP) 2.5 times more frequently than in patients without early-onset VAP. On the other hand, a cohort study by Rouze et al [ 39 ] found that among COPD patients mechanically ventilated in Europe and Latin America, neither VAP nor VAT were more frequent. Moreover, among patients with VA-LRTI, Escherichia coli and Stenotrophomonas maltophilia were found at significantly higher rates in COPD patients.…”
Section: Vulnerable Patients At Risk For Nosocomial Infectionsmentioning
confidence: 99%
“…However, what is clinically useful is that PA occurred in Early onset-VAP (Eo-VAP) 2.5 times more frequently than in patients without early-onset VAP. On the other hand, a cohort study by Rouze et al [ 39 ] found that among COPD patients mechanically ventilated in Europe and Latin America, neither VAP nor VAT were more frequent. Moreover, among patients with VA-LRTI, Escherichia coli and Stenotrophomonas maltophilia were found at significantly higher rates in COPD patients.…”
Section: Vulnerable Patients At Risk For Nosocomial Infectionsmentioning
confidence: 99%
“…According to previous studies, COPD is a commonco-morbidity in patients with VAP (18,19). However, it was demonstrated that the presence of COPD is not associated with a higher incidence of VAP as compared with that of patients without COPD (1,12). Over the last decades, several studies have attempted to assess the impact of COPD on the outcomes of patients with VAP.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were admitted to the ICUs for both medical and surgical reasons. The included studies did not report any statistically significant differences in patient co-morbidities between COPD and non-COPD patients, except for that by Rouze et al (1), which reported a significant difference in the number of diabetics. Furthermore, disease severity was significantly higher in the COPD group in the study of Makris et al (16).…”
Section: Study Search and Selectionmentioning
confidence: 97%
See 1 more Smart Citation
“…MDR pathogens are usually implicated in nosocomial infections. Rouzé et al conducted an ancillary analysis of a prospective multicenter study on the impact of chronic obstructive pulmonary disease (COPD) in ventilator-associated lower respiratory tract infections, and found that the rate of MDR bacteria was not significantly different between COPD and non-COPD patients, while Escherichia coli and Stenotrophomonas maltophilia were significantly more frequent in COPD patients [ 2 ]. A retrospective five-year single cohort observational study on the epidemiology of MDR infection in 73 oncological patients by Perdikouri et al showed that the most frequently isolated pathogens were carbapenem-resistant Klebsiella pneumoniae , methicillin-resistant Staphylococcus aureus (MRSA) and carbapenem-resistant Acinetobacter baumannii , while infection-associated mortality was as high as 32% [ 3 ].…”
mentioning
confidence: 99%